An Assessment of the Relationship Between Speed and Road Safety - Etika, Anderson A.; Adeke, Paul T.; Ubana, Gabriel O. (Transactions on Engineering and Computing Sciences, 2023)
Despite research showing a connection between vehicle speed and crash severity and risk, the leading cause of traffic crashes and fatalities worldwide continues to be driving at speeds that are illegal or unsuitable. An overview of the relationship between vehicle speed and road safety in relation to crash involvement and crash severity is given in this study. Additionally, it examines and emphasizes the Power Model’s applicability and effectiveness in projecting safety gains from speed increases. According to the paper’s summary, there is still a significant association between speed and road safety. Yet, because of the moderating effects of several factors, it is difficult to quantify the exact relationship between speed and crash rate and injury severity. But it is generally acknowledged that speed both directly and indirectly affects crash rates and raises the severity of damage or fatality.